1996
DOI: 10.1046/j.1464-410x.1996.19313.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombelastographic evaluation of coagulation in transurethral prostatectomy

Abstract: Objective To assess the changes in overall coagulation status and define the degree of systemic fibrinolysis occurring in patients undergoing transurethral prostatectomy (TURP). Patients and methods Thirty patients undergoing TURP, 23 for benign prostatic hyperplasia and seven for prostatic carcinoma, were studied prospectively. Serial venous blood samples were taken using the two‐syringe technique. Samples were taken before, during and at intervals up to 72 h and 10–14 days after surgery. Thrombelastography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…, 1997). Hypercoagulable TEG ® results (reduced clot time, increased alpha angle and clot strength) (Figure 3) have been found in other surgical studies (Bell et al. , 1996; Goobie et al.…”
Section: Other Surgical Proceduressupporting
confidence: 74%
“…, 1997). Hypercoagulable TEG ® results (reduced clot time, increased alpha angle and clot strength) (Figure 3) have been found in other surgical studies (Bell et al. , 1996; Goobie et al.…”
Section: Other Surgical Proceduressupporting
confidence: 74%
“…This has the additional benefit of measuring fibrinolytic activity and thus assesses global coagulation from clot formation to fibrinolysis by generation of a TEMogram [17]. Currently, both TEG and ROTEM are used in clinical practice to evaluate haemostasis, monitor bleeding and guide transfusion in patients with trauma, cardiac disease and those undergoing surgery [18][19][20][21][22]. Furthermore, ROTEM has been used to identify hypercoagulability in pregnancy [23,24], suggesting that it has use in quantifying both hypo-and hypercoagulable states.…”
Section: Introductionmentioning
confidence: 99%
“…Bell et al [19] reported that the thromboelastogrphy (TEG) parameters reflect a hypercoagulable state during and after TURP and that this change is caused by the inhibition of the fibrinolytic system. Conversely, Nielsen et al [20] concluded that the fibrinolytic system is activated during TURP due to surgical trauma.…”
Section: Discussionmentioning
confidence: 99%